Behaviour of the Structure during the Fire - Gillie, Martin; Stratford, Tim J (The University of Edinburgh, 2007)
the understanding of the global behaviour of heated concrete structures has received relatively little attention. This is in part due to the lack of experimental data on complete concrete structures in fire and in part due to the difficulties associated with numerical modelling of concrete structures. Fire tests on concrete structures are infrequent. Prior to the Dalmarnock test discussed here, the most complete set of test data available was that produced by a fire test on the reinforced concrete frame at Cardington, UK (Bailey, 2002; Canisius et al., 2003). Unfortunately this test suffered from instrumentation failure prior to the end of the test and so the dataset is incomplete. More recently, a number of tests have been conducted on model-scale concrete slabs with the aim of verifying design methods for composite structures in fire. However, the data available on heated concrete structures until the Dalmarnock tests remained very limited. In order to alleviate this lack of data, the Dalmarnock structure was heavily instrumented prior to Test One. The type of instrumentation installed, the results and their implications are the focus of this chapter. Dalmarnock Test One was the first structural test on a heated concrete structure in which both the fire and the structure were instrumented.
Chapter 8 in the book: The Dalmarnock Fire Tests: Experiments and Modelling, Edited by G. Rein, C. Abecassis Empis and R. Carvel, Published by the School of Engineering and Electronics, University of Edinburgh, 2007. ISBN 978-0-9557497-0-4
Keywords: Dalmarnock; Experiment